Pembiasaan pola hidup sehat melalui program Sabtu Sehat di SMPN 4 Silo kabupaten Jember. - Prasojo, Amin; Sulaiman, Ahmad (STIE Jambatan Bulan, 2025)
Maintaining health is important, unhealthy lifestyles such as lack of exercise, poor diet, and lack of hygiene can trigger various chronic diseases, therefore, efforts are needed to increase public awareness and interest in health, one of the efforts that can be made is to routinely carry out routine sports activities, a healthy and regular diet, and maintain the cleanliness of the surrounding environment. Our service activity is when after we conducted a survey or observation at SMPN 4 Silo school we found several problems in students, especially in their lifestyle at school, namely the lack of healthy lifestyle patterns such as lack of exercise, eating unhealthy food or junkfood and a less clean environment. Especially at the age of adolescence, smpn 4 silo students must learn to maintain their health and hygiene, starting from lifestyle, diet to awareness of the cleanliness of the environment around them. Therefore, we took the initiative to create a routine Healthy Saturday activity program with the hope of introducing healthy lifestyle activities that can be started from exercising, a healthy, nutritious and regular diet, and making them aware of the importance of environmental cleanliness, both at home and at school.